2006
DOI: 10.1039/b612944g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and olefination of carbonyl compounds using solid-supported reagents

Abstract: The development and application of three new solid-supported reagents for use in the synthesis or olefination of carbonyl compounds are described. The reagents include the Weinreb amide, Mukaiyama's S-2-pyridyl thioate and a Peterson methylenation reagent. As solid-supports p-benzyl alcohol resin, Wang resin and Merrifield resin (1-2% crosslinked polystyrene) have been used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The reaction of 1,10-phenanthroline (9.0 mg, 0.05 mmol), 2,2'-bipyridine (8.0 mg, 0.05 mmol), CuCl (9.8 mg, 0.10 mmol), K 2 CO 3 (34.2 mg, 0.25 mmol), dry toluene (2.5 mL), DBAD (22.7 mg, 0.10 mmol), and 1g (87.2 mg, 0.5 mmol)/dry toluene (2.5 mL) afforded 2g [28] . The reaction of 1,10-phenanthroline (4.4 mg, 0.025 mmol), 2,2'-bipyridine (3.8 mg, 0.025 mmol), CuCl (5.0 mg, 0.05 mmol), K 2 CO 3 (34.2 mg, 0.25 mmol), dry toluene (2.5 mL), DBAD (11.7 mg, 0.05 mmol), and 1g (87.0 mg, 0.5 mmol)/dry toluene (2.5 mL) afforded 2g [28] (71.2 mg, 83%) (eluent: petroleum ether∶ethyl acetate =30∶1): Liquid.…”
Section: -Phenylhex-2-yn-1-one (2g)mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of 1,10-phenanthroline (9.0 mg, 0.05 mmol), 2,2'-bipyridine (8.0 mg, 0.05 mmol), CuCl (9.8 mg, 0.10 mmol), K 2 CO 3 (34.2 mg, 0.25 mmol), dry toluene (2.5 mL), DBAD (22.7 mg, 0.10 mmol), and 1g (87.2 mg, 0.5 mmol)/dry toluene (2.5 mL) afforded 2g [28] . The reaction of 1,10-phenanthroline (4.4 mg, 0.025 mmol), 2,2'-bipyridine (3.8 mg, 0.025 mmol), CuCl (5.0 mg, 0.05 mmol), K 2 CO 3 (34.2 mg, 0.25 mmol), dry toluene (2.5 mL), DBAD (11.7 mg, 0.05 mmol), and 1g (87.0 mg, 0.5 mmol)/dry toluene (2.5 mL) afforded 2g [28] (71.2 mg, 83%) (eluent: petroleum ether∶ethyl acetate =30∶1): Liquid.…”
Section: -Phenylhex-2-yn-1-one (2g)mentioning
confidence: 99%
“…The reaction of 1,10-phenanthroline (4.4 mg, 0.025 mmol), 2,2'-bipyridine (3.8 mg, 0.025 mmol), CuCl (5.0 mg, 0.05 mmol), K 2 CO 3 (34.2 mg, 0.25 mmol), dry toluene (2.5 mL), DBAD (11.7 mg, 0.05 mmol), and 1g (87.0 mg, 0.5 mmol)/dry toluene (2.5 mL) afforded 2g [28] (71.2 mg, 83%) (eluent: petroleum ether∶ethyl acetate =30∶1): Liquid.…”
Section: -Phenylhex-2-yn-1-one (2g)mentioning
confidence: 99%
“…Recently, the Tanner research group 64 reported the development and applications of three new solid-supported reagents for the synthesis of carbonyl compounds and olefins.…”
Section: Scheme 37 a Polymer-assisted Sonogashira Reactionmentioning
confidence: 99%
“…Reduction of chiral O,N-disubstituted hydroxylamines offers easy access to optically active primary amines and polyfunctional amines. The acylation of O,N-dimethylhydroxylamine affords Weinreb amides,[595][596][597][598][599] which serve as carbonyl equivalents and are extensively used in the preparation of ketones, aldehydes, and 1,2-diols. O,N-Disubstituted hydroxylamines may display bioactivity in their own right as bioisosteres of the corresponding amines or contribute to bioactivity, generally to enzyme inhibition, as an essential structural motif.…”
mentioning
confidence: 99%